2021
DOI: 10.1101/2021.05.14.443822
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fast-spiking interneurons of the premotor cortex contribute to action planning

Abstract: Planning and execution of voluntary movement depend on the contribution of distinct classes of neurons in primary motor and premotor areas. However, the specific functional role of GABAergic cells remains only partly understood. Here, electrophysiological and computational analyses are employed to compare directly the response properties of putative pyramidal (PNs) and fast-spiking, GABAergic neurons (FSNs) during licking and forelimb retraction in mice. Recordings from anterolateral motor cortex and rostral f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Although we might expect that activation of vmPFC PV neurons would release reactive behaviors such as freezing by suppressing vmPFC outputs, the relationship between PV and pyramidal neuron firing is complex. Cortical PV neurons have been reported to activate simultaneously with local pyramidal neurons (Estebanez et al, 2017;Giordano et al, 2021;Isomura et al, 2009;Merchant et al, 2008;Nashef et al, 2020;Okun and Lampl, 2008;Pinto and Dan, 2015), and it has been suggested that PV neurons may help to shape, rather than gate, the firing of local pyramidal neurons (Isomura et al, 2009;Merchant et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although we might expect that activation of vmPFC PV neurons would release reactive behaviors such as freezing by suppressing vmPFC outputs, the relationship between PV and pyramidal neuron firing is complex. Cortical PV neurons have been reported to activate simultaneously with local pyramidal neurons (Estebanez et al, 2017;Giordano et al, 2021;Isomura et al, 2009;Merchant et al, 2008;Nashef et al, 2020;Okun and Lampl, 2008;Pinto and Dan, 2015), and it has been suggested that PV neurons may help to shape, rather than gate, the firing of local pyramidal neurons (Isomura et al, 2009;Merchant et al, 2012).…”
Section: Introductionmentioning
confidence: 99%